Fundamentals of Systematic Zoology - Paul, Nishit Kumar (University Journal of Zoology, Rajshahi University, 2010)
Title: Fundamentals of Systematic Zoology Author: Md. Ataur Rahman Khan Publisher Zahirul Islam (Lipton), Aligarh Library, Rajshahi. March, 2010, Pp. 380. DOI: 10.3329/ujzru.v28i0.5295 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 83